Angiomyolipoma of the Thoracic Wall: An Extremely Rare Diagnostic Challenge - Georgios Gemenetzis; Eleni Kostidou; Kalliroi Goula; Vassilios Smyrniotis; Nikolaos Arkadopoulos (Case Reports in Surgery)
Extrarenal angiomyolipoma (AML) is an extremely uncommon lesion, accounting for less than 9% of all angiomyolipomas. We present a previously unreported case of a rarely located gigantic extrarenal angiomyolipoma at the posterolateral chest wall of a 35-year-old woman. Clinically, the lesion had all the characteristics of a benign tumor, being soft in palpation, painless, and growing in size in a slow rate. Histologically, the lesion consisted of convoluted thick-walled blood vessels without an elastic layer, interlacing fascicles of smooth muscle, and mature adipose tissue, features consistent with an angiomyolipoma. The mass was surgically removed, without any postoperative complications, and the patient has an uneventful postoperative course. Signs of local recurrence have not been observed. The purpose of this brief report is to point out the necessity of including angiomyolipoma in the differential diagnosis of adipose layer lesions.